Political Motives for the Plan for the Expansion of New Autonomous Regions in Papua - Dafrin Muksin; Sahrail Robo; Ahmad Rizali Pawane (Politicon : Jurnal Ilmu Politik, 2021)
This study examines the political motives of the plan to expand the new autonomous region in Papua. This is because the expansion of new autonomous areas is not always purely for the welfare of the people but is very closely related to political interests, namely power, and position. This study used qualitative research methods. The data used in the form of secondary data was obtained through reputable media and documents in journals. Next, the data is sorted to form a systematic framework. To analyze the research data, Nvivo plus 12 was used. From the analysis, it was described, and a conclusion was drawn. The study results indicate that the political motives for the plan to expand the new autonomous region in Papua are very material-intensive, namely the interests of the political elite, both central and local, to obtain rewards, position, and power. There is a narrative in the ideological incentive motive that regional expansion is for the public interest, namely providing services, developing infrastructure, increasing human resources, and alleviating poverty. However, in reality, some of the ongoing divisions in Papua have not yet impacted the Papuan people.